2015
DOI: 10.3390/ijerph13010010
|View full text |Cite
|
Sign up to set email alerts
|

Glyceollin I Reverses Epithelial to Mesenchymal Transition in Letrozole Resistant Breast Cancer through ZEB1

Abstract: Although aromatase inhibitors are standard endocrine therapy for postmenopausal women with early-stage metastatic estrogen-dependent breast cancer, they are limited by the development of drug resistance. A better understanding of this process is critical towards designing novel strategies for disease management. Previously, we demonstrated a global proteomic signature of letrozole-resistance associated with hormone-independence, enhanced cell motility and implications of epithelial mesenchymal transition (EMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 36 publications
3
27
0
Order By: Relevance
“…Glyceollin has shown to reduce invasion and migration properties of letrozole resistant breast cancer cells via its inhibitory effect on ZEB1. In vivo study also reveals lower ZEB1 expression in tumors of glyceollin‐treated animals (Carriere et al, ). This mechanism of glyceollin might be useful in glioma therapy.…”
Section: Prospective Natural Compounds In Gliomamentioning
confidence: 94%
“…Glyceollin has shown to reduce invasion and migration properties of letrozole resistant breast cancer cells via its inhibitory effect on ZEB1. In vivo study also reveals lower ZEB1 expression in tumors of glyceollin‐treated animals (Carriere et al, ). This mechanism of glyceollin might be useful in glioma therapy.…”
Section: Prospective Natural Compounds In Gliomamentioning
confidence: 94%
“…There have been advancements in chemotherapeutic agents over the past decade; however, there is still an urgent need to overcome drug resistance. Numerous studies have focused on phytochemicals, which are nonnutritive plant chemicals that have disease-protective or -preventive properties (12)(13)(14). These chemicals are non-essential nutrients, meaning they are not required by the human body for sustaining life (15).…”
Section: Phytochemicals and Breast Cancermentioning
confidence: 99%
“…Due to the inherently resistant nature of BCSCs and their involvement in metastasis, it is increasingly imperative to develop therapies able to directly target these cells. While it is understood that certain soy phytochemicals, including glyceollins, target the EMT (14,73) (Fig. 2), their impact on BCSCs remains unclear.…”
Section: Current Status and Implications Of Phytochemicals As Potentimentioning
confidence: 99%
“…Carriere and collaborators [2] studied the role of glyceollin I in the treatment of Letrozole resistant breast cancer. They found that letrozole-resistance increased Zinc Finger E-Box Binding Homeobox 1 (ZEB1) expression by about 4 fold, while glyceollin I treatment caused a 4-fold reduction.…”
mentioning
confidence: 99%